Виртуальный лабораторный стенд для обучения по дисциплине "Методы расчета и моделирования преобразователей" - Жемеров, Г.Г.; Ильина, H.A.; Ковальчук, О.И.; Крылов, Д.С. (Електротехніка і електромеханіка, 2011)
A virtual laboratory bench based on PC and Matlab/Simulink/Power System BlockSet programs is described. The bench is intended for reseach on an autonomous parallel current inverter.